The Relationship Between the Knowledge Level of Balanced Nutrition and Body Mass Index : A Case Study of Indonesian School Students in Kuala Lumpur - Teesen, Gabriele Stefhany; Yuliani, Anita; Syabariyah, Sitti; Yualita, Perla; Herosandiana, Aef (The Indonesian Institute of Science and Technology Research, 2024)
Nutrition is a critical issue in any country as it can impact the growth and development of children. To ensure that children have a balanced diet, education on nutrition should begin at a young age, ideally when they enter school. With good nutrition knowledge, children are more likely to have a healthy body proportionate to their age. This study aimed to determine the link between elementary school students' knowledge level in Sekolah Indonesia Kuala Lumpur (SIKL) about nutrition and their Body Mass Index. The research used a cross-sectional approach with a correlation method, and the total population was 220 students. The sampling technique used was purposive sampling, and 96 students were selected based on inclusion and exclusion criteria. Data collection was through a questionnaire, which was then analyzed using univariate and bivariate analysis, including chi-square statistical tests. The study found a relationship between the level of nutrition knowledge and Body Mass Index in SIKL students, with a p-value of 0.000 < α 0.05. To improve the level of knowledge of primary school children, it is highly recommended to provide education on balanced nutrition.